Amination catalyst, preparation method and application thereof
By using the aminating catalyst Mo12CrmBixVyMzOg, the problem of molybdenum volatilization caused by high heat spots in the oxidation reaction was solved, and the long life and efficient stability of the catalyst were achieved.
Patent Information
- Application Number
- CN202310000365.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-03
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-01-03
AI Technical Summary
In the oxidation reaction, the molybdenum-based catalyst volatilizes molybdenum due to the formation of high hot spots, and the catalyst is deactivated, which requires frequent replacement, which affects production efficiency and environmental safety.
The amination catalyst Mo12CrmBixVyMzOg is used to control the reaction conditions and supergravity pretreatment to form a catalyst with a uniform particle size to improve the activity and stability of the catalyst.
The life of the catalyst is extended, the reaction temperature is reduced, the yield of the target product is increased, the volatility of molybdenum is reduced, and the resistance and stability of the catalyst is improved.
Smart Images

Figure BDA0004034235930000121 
Figure BDA0004034235930000131
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalysts, and in particular to an amination catalyst, a preparation method thereof and application thereof. Background Art
[0002] Nitrile products are important basic organic chemical raw materials, and play a decisive role in the adjustment of future energy structure and the development of chemical industry. Modern industrial nitrile production mainly adopts gas phase amination method. For example, methanol amination is used to produce hydrocyanic acid, allyl amination is used to prepare acrylonitrile, and xylene amination is used to prepare phthalonitrile.
[0003] In the oxidation process, nitriles are generally produced in a tube reactor. A tube reactor usually consists of 10-20,000 metal tubes filled with solid catalyst particles of a certain morphology and cooled by oil or molten salt as a heat transfer fluid. Since the reaction is highly exothermic, it is difficult to obtain a uniform bed temperature distribution. Generally, such oxidation reactions form hot spots in the reaction zone.
[0004] The catalysts used in the oxide process are mainly molybdenum-based catalysts, such as a mixture of iron molybdate Fe2(MoO4)3 and molybdenum trioxide MoO3, wherein the atomic ratio of Mo:Fe is between 0.1 and 3. In most aspects, the catalytic performance is satisfactory; the product yield is high (generally more than 90%), and since molybdenum and iron are both very low in toxicity, the impact on the environment and human health is limited.
[0005] However, due to the formation of hot spots in the oxidation reaction, molybdenum is volatilized from the catalyst, thereby deactivating the catalyst. Molybdenum sublimates from the upper part of the reactor where the methanol concentration is high and decomposes in the lower part of the reactor to form needle-shaped MoO3 crystals. As a result of molybdenum sublimation and concentration / decomposition, catalytic activity and main product selectivity decrease and the pressure drop in the reactor increases. Therefore, the catalyst needs to be replaced frequently. Summary of the invention
[0006] In order to achieve the above-mentioned purpose, the present invention provides an amination catalyst and a preparation method thereof.
[0007] An amination catalyst having the structure: Mo 12 Cr m Bi x V y M z O g, M is one or more of Al, Na, K, Fe, P, B, Sb, Si, Ni, Pr, Mg, Cs, Nd, Ce, Ca, Ti, Cu, preferably one or more of Al, Na, K, Fe, P, B, Sb, Si, Ni, Pr, Mg, Cs, Pr, wherein 0<m≤300, preferably 150≤m≤250; 0<x<10, preferably 1<x<5; 0<y≤250, preferably 120≤y≤240; and 0<z≤9000, preferably 5000≤z≤8600, g represents the number of oxygen atoms in the balanced cationic valence state, and g ranges from 0<g≤20000;
[0008] A method for preparing an amination catalyst comprises the following steps:
[0009] a) Adding a molybdenum source, a chromium source, a bismuth source, a vanadium source and an aqueous solution of an M source into a reaction kettle, the temperature of which is maintained at 60° C. to 95° C.
[0010] b) Under the condition of rapid stirring, the raw material solution is added to the reaction kettle, and the pH value of the precipitation process is controlled at 1.0-3.0, preferably 1-2.8, with alkali or acid. After the precipitation and impregnation are completed, aging is performed for 2-12 hours.
[0011] c) The catalyst solution is mixed evenly, and the catalyst solution is added into a supergravity machine, and supergravity pretreatment is performed under the conditions of a frequency of 10 Hz-35 Hz, a gravity acceleration range of 3-40 G, and a temperature of 50° C.-120° C. to obtain a catalyst precursor, and then drying.
[0012] d) calcining the catalyst powder at 400°C to 600°C for 10 to 20 hours to obtain a finished catalyst.
[0013] Preferably, based on 12 mole parts of molybdenum in the molybdenum source, the mole parts of chromium added in the chromium source are 0-300 parts, wherein the amount of chromium source added is not 0, preferably 150-250 parts;
[0014] The molar proportion of bismuth added to the bismuth source is 0-10 parts, wherein the added amount is not 0, preferably 1-5 parts;
[0015] The molar proportion of vanadium added to the vanadium source is 0-250 parts, wherein the added amount is not 0, preferably 120-240 parts;
[0016] The total added molar portion of metal M in the M source is 0-9000 parts, wherein the added amount is not 0, preferably 5000-8600 parts.
[0017] The molybdenum source of the catalyst described in the present invention is selected from one or more molybdenum-containing compounds such as ammonium polymolybdate, molybdenum trioxide, molybdic acid and molybdenum disulfide, and is preferably water-soluble molybdenum salt ammonium polymolybdate.
[0018] The chromium source of the catalyst of the present invention is selected from chromium trioxide, dichromic acid, chromium oxalate or other chromium salts.
[0019] The vanadium source of the catalyst of the present invention is selected from vanadium pentoxide, vanadium tetroxide, vanadium trioxide, ammonium metavanadate, sodium metavanadate, etc., preferably vanadium pentoxide.
[0020] The bismuth source of the catalyst of the present invention is selected from bismuth nitrate, bismuth carbonate or organic acid bismuth, preferably bismuth nitrate.
[0021] The cesium element in the catalyst of the present invention is derived from one or more of cesium carbonate, cesium hydroxide, cesium nitrate and cesium chloride, preferably cesium nitrate and cesium carbonate.
[0022] The rapid stirring condition in step b) refers to a stirring speed of 50 r / min-1500 r / min, preferably 200-800 r / min.
[0023] If more than one element is desired in the catalyst, two or three well-stirred solutions are mixed together before homogenization. If necessary, the solutions may be heated and / or the pH adjusted by adding, for example, ammonia, HNO3, H2SO4 and / or HCl in order to obtain a uniform mix of the elements.
[0024] When the pH is sufficiently raised by adding a base such as NH3 and / or NaOH, a solid precipitate is obtained. If necessary, in order to simplify the separation of the solid from the liquid phase by increasing the size of the precipitate, the temperature of the liquid containing the precipitate is raised to 35-100°C, usually 40-70°C. When the pH is adjusted by adding an acid such as HNO3, H2SO4 and / or HCl, the growth of the precipitate particle size is further promoted by raising the temperature of the precipitate liquid, which is raised to 75-100°C, usually 87-97°C.
[0025] A magnetic actuator is provided in the ultra-gravity machine, the frequency of the magnetic actuator is 10Hz-35Hz, the gravity acceleration range is 3-40G, the temperature is 50℃-120℃, and the catalyst precursor is obtained after ultra-gravity pretreatment. The catalyst precursor is placed in an oven at 105℃-190℃ and dried for 10-28 hours to obtain the catalyst precursor, and the catalyst powder is obtained after airflow classification.
[0026] Preferably, a packing layer is provided inside the rotating device of the supergravity device.
[0027] In the step d), the calcination temperature is preferably 400-550° C. Preferably, a reducing agent and an oxidizing agent are optionally added during calcination, wherein the reducing agent is selected from H2 and / or CO, and the oxidizing agent is selected from H2O and / or CO2.
[0028] Preferably, an inert agent is added during calcination, and the inert agent is He, Ne, N2, Ar and / or Kr. The gas volume compositions of the reducing, oxidizing and inert agents are 0-50 vol.%, 0-50 vol.% and 99.99-0 vol.%, respectively.
[0029] The catalyst has 4-45m 2 / g specific surface area (BET), more preferably 5-25m 2 / g, most preferably 5.5-15m 2 / g.
[0030] The present invention also provides the application of the amination catalyst, which can be used for the amination of low-carbon alcohols or hydrocarbons, especially the amination reaction of alcohols below C5, hydrocarbons below C5 or C7-C9 aromatic hydrocarbons to prepare nitriles.
[0031] The active elements are evenly distributed, Mo volatility is stable, and after a small amount of Mo element on the surface evaporates, the Mo element inside the catalyst can migrate to the catalyst surface to supplement the loss of Mo element on the catalyst surface, and the catalyst has high anti-toxicity.
[0032] The molybdenum element in the catalyst of the present invention is more stable and less volatile, and the catalyst has a uniform particle size distribution. In addition, the application of supergravity technology can greatly reduce the scale of traditional factories, making them develop in the direction of miniaturization and indoorization, and will bring more revolutionary changes in the industrial field. The shear stress of the filler on the liquid in the supergravity field causes the liquid to be divided into an extremely thin liquid film and tiny droplets. The catalyst liquid solution constantly changes direction due to the rotation of the filler. When the rotating filler layer passes through the curved and narrow channels, the air infiltrates, wraps, accumulates, and captures the particles and droplet components in the catalyst liquid solution, and the filler has a filtering effect on the catalyst liquid solution, providing a good place for gas-liquid-solid separation in the catalyst liquid solution. The supergravity field catalyst preparation process integrates the mechanisms of inertial collision, filtration separation, centrifugal separation, washing absorption, etc., and realizes the high-efficiency preparation of uniform particle size catalysts.
[0033] The present invention has the following technical effects:
[0034] (1) The present invention can reduce the reaction temperature and improve the yield of the target product by adding M metal oxide.
[0035] (2) Precise control of the catalyst preparation process can better form uniform particle size crystalline catalysts and reduce irregular particle catalysts, thereby improving the activity and stability of the catalyst and extending the life of the catalyst.
[0036] (3) The discovery that a catalyst having a polyhedral structure composed of a combination of a certain amount of chromium cations, bismuth and molybdenum has these desired properties is a rather unexpected technical effect. In addition to showing a high selectivity (>93%) for obtaining hydrocyanic acid from methanol, ammonia and oxygen in an inert medium, no volatilization of bismuth or molybdenum from the catalyst of the present invention was detected after 30 days at 300°C in a flowing gas atmosphere of 6% methanol and 8% ammonia, 8% oxygen and the rest nitrogen. DETAILED DESCRIPTION
[0037] The present invention is further described below by way of examples, but the present invention is not limited to the following examples.
[0038] Preferably, a packing layer is provided inside the rotating device of the ultra-gravity machine. Under the action of pressure difference, air enters the packing layer axially from the bottom of the device. After the liquid in the circulation tank is sent into the device by a centrifugal pump, it is evenly sprayed radially on the inner edge of the packing layer through a liquid distributor. Under the action of centrifugal force, the liquid is thrown toward the inner wall of the device. In the packing of the device, gas and liquid achieve cross-flow contact and absorption. After the gas is purified, it is discharged from the top gas outlet of the device. The liquid and the impurities that have escaped are discharged from the liquid outlet under the action of gravity and flow into the circulation tank.
[0039] Example 1
[0040] 70g of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O 24 ·4H20) was ultrasonically dissolved in 365g pure water, and solution A was obtained after complete dissolution. 495.55g CrO3 (chemical formula is CrO3), 13.05g bismuth nitrate (chemical formula is Bi(NO3)3), and 721.1g vanadium pentoxide (V2O5) were dissolved in 1200g pure water to obtain solution B. Auxiliary agents 0.66g calcium carbonate (chemical formula is CaCO3), 1.14g potassium carbonate (K2CO3), 68.56g phosphoric acid (commercially available 85%wt phosphoric acid, the same below), 84252.4g 20% silica sol were dissolved in 70000g pure water to obtain solution C. The aqueous solution of raw material A was added to the reactor, and the temperature of the reactor was maintained at 75°C. Under rapid stirring, the solution of raw material B was added to the reactor. After the precipitation impregnation is completed, aging is performed. Then, solution C was added, the frequency of the magnetic transmission of the supergravity machine was 20Hz, the gravity acceleration range was 10G, and the temperature was 75℃. After supergravity pretreatment, the catalyst precursor was obtained, which was placed in an oven at 150℃ for 24 hours to obtain the catalyst precursor, and the catalyst powder was obtained after airflow classification. The catalyst powder was calcined at 600℃ for 10h to obtain the finished catalyst sample 1. The element ratio of sample 1 is shown in Table 2.
[0041] Oxidation test evaluation
[0042] 25g of finished catalyst was loaded into a 50cm long reactor, where the reaction tube was a 25mm stainless steel reaction tube. The catalyst pretreatment process was as follows: firstly, air was introduced at a volume space velocity of 8000h -1 The temperature of the reaction tube was heated from room temperature to 250°C at a heating rate of 5°C / min and maintained for 120 min, then switched to nitrogen purge for 180 min at a purge volume space velocity of 1000 h -1 After the catalyst pretreatment is completed, the mixture is heated to 1:50:9 (molar ratio) at a volume space velocity of 3000 h -1 The amination reaction was carried out under the conditions of (standard state), temperature of 430°C and normal pressure. Reaction results: the initial xylene conversion rate was 99%, the phthalonitrile selectivity was 84.9%, and after 2000h of operation, the xylene conversion rate was 98.8%, and the phthalonitrile selectivity was 84.7%.
[0043] Example 2
[0044] 70g of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O 24 ·4H20) was ultrasonically dissolved in 365g of pure water, and solution A was obtained after complete dissolution. 26.7g of iron nitrate (Fe(NO3)3·9H2O), 825.9g of CrO3 (chemical formula CrO3), 65.25g of bismuth nitrate (chemical formula Bi(NO3)3), and 360.56g of vanadium pentoxide (V2O5) were dissolved in 1500g of pure water to obtain solution B. Auxiliary agents 1.08g of cesium carbonate (chemical formula Cs2CO3), 2.28g of potassium carbonate (K2CO3), 95.23g of phosphoric acid, and 49560.2g of 20% silica sol were dissolved in 50000g of pure water to obtain solution C. The aqueous solution of raw material A was added to the reactor, and the temperature of the reactor was maintained at 85°C. Under rapid stirring, the solution of raw material B was added to the reactor. After the precipitation impregnation was completed, aging was performed, and then solution C was added. The frequency of the magnetic transmission of the supergravity machine is 35Hz, the gravity acceleration is 5G, and the temperature is 65℃. The catalyst precursor is obtained after supergravity pretreatment, and is placed in an oven at 190℃ for 14 hours to obtain the catalyst precursor. The catalyst powder is obtained after airflow classification. The catalyst powder is calcined at 550℃ for 15h to obtain the finished catalyst sample 2. The element ratio of sample 2 is shown in Table 2.
[0045] Oxidation test evaluation
[0046] The evaluation method is the same as that of Example 1, and the evaluation results are listed in Table 1.
[0047] Example 3
[0048] 70g of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O 24·4H20) was ultrasonically dissolved in 365g pure water, and solution A was obtained after complete dissolution. 925g CrO3 (chemical formula is CrO3), 104.4g bismuth nitrate (chemical formula is Bi(NO3)3), and 751.17g vanadium pentoxide (V2O5) were dissolved in 2800g pure water to obtain solution B. 3.3g calcium carbonate (chemical formula is CaCO3), 5.25g sodium carbonate (Na2CO3), 114.3g phosphoric acid, 14.4g antimony trioxide, and 87226g 20% silica sol were dissolved in 90000g pure water to obtain solution C. The aqueous solution of raw material A was added to the reactor, and the temperature of the reactor was maintained at 90°C. Under rapid stirring, the solution of raw material B was added to the reactor. After the precipitation impregnation is completed, aging is carried out, and then solution C is added. The frequency of the magnetic transmission of the supergravity machine is 15Hz, the temperature is 55℃, and the gravity acceleration is 6G. The catalyst precursor is obtained after supergravity pretreatment, and is placed in an oven at 110℃ for 12 hours to obtain the catalyst precursor. The catalyst powder is obtained after airflow classification. The formed strip catalyst is calcined at 530℃ for 11h to obtain the finished catalyst sample 3. The element ratio of sample 3 is shown in Table 2.
[0049] Oxidation test evaluation
[0050] The evaluation method is the same as that of Example 1, and the evaluation results are listed in Table 1.
[0051] Example 4
[0052] 70g of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O 24·4H20) was ultrasonically dissolved in 365g of pure water, and solution A was obtained after complete dissolution. 133.48g of iron nitrate (Fe(NO3)3·9H2O), 660.74g of CrO3 (chemical formula CrO3), 26.1g of bismuth nitrate (chemical formula Bi(NO3)3), and 540.84g of vanadium pentoxide (V2O5) were dissolved in 2600g of pure water to obtain solution B. 0.34g of potassium carbonate (K2CO3), 42.26g of nickel nitrate (chemical formula Ni(NO3)2), 4.41g of magnesium nitrate (Mg(NO3)2), 3.5g of strontium nitrate (Sr(NO3)2), and 59472g of 20% silica sol were dissolved in 50000g of pure water to obtain solution C. The aqueous solution of raw material A was added into the reactor, and the temperature of the reactor was maintained at 90°C. Under the condition of rapid stirring, the raw material B solution was added to the reactor, and after precipitation and impregnation, it was aged for 6 hours, and then solution C was added. The frequency of the magnetic transmission of the ultra-gravity machine was 40Hz, the temperature was 100℃, and the gravity acceleration was 20G. After ultra-gravity pretreatment, the catalyst precursor was obtained, which was placed in an oven at 160℃ for 17 hours to obtain the catalyst precursor, and the catalyst powder was obtained after airflow classification. The formed strip catalyst was roasted at 540℃ for 10 hours to obtain the finished catalyst sample 4.
[0053] The ratio of the four elements in the samples is shown in Table 2.
[0054] Oxidation test evaluation
[0055] 25g of finished catalyst was loaded into a 50cm long reactor, where the reaction tube was a 25mm stainless steel reaction tube. The catalyst pretreatment process was as follows: firstly, air was introduced at a volume space velocity of 8000h -1 The temperature of the reaction tube was heated from room temperature to 250°C at a heating rate of 5°C / min and maintained for 120 min, then switched to nitrogen purge for 180 min at a purge volume space velocity of 1000 h -1 After the catalyst pretreatment is completed, the xylene: air: ammonia = 1:40:5 (molar ratio), volume space velocity 4000h -1 The amination reaction was carried out under the conditions of (standard state), temperature of 430°C and normal pressure. Reaction results: the initial xylene conversion rate was 99.2%, the phthalonitrile selectivity was 85.6%, and after 2000h of operation, the xylene conversion rate was 99%, and the phthalonitrile selectivity was 85%.
[0056] The evaluation results are listed in Table 1.
[0057] Example 5
[0058] 70g of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O 24·4H20) was ultrasonically dissolved in 365g pure water, and solution A was obtained after complete dissolution. 264.3g CrO3 (chemical formula is CrO3), 1.3g bismuth nitrate (chemical formula is Bi(NO3)3), and 721.1g vanadium pentoxide (V2O5) were dissolved in 3000g pure water to obtain solution B. Auxiliary agents 0.54g cesium carbonate (chemical formula is Cs2CO3), 0.35g sodium carbonate (Na2CO3), 19g phosphoric acid, 9.63g antimony trioxide, 3.5g strontium nitrate, 29736.1g 20% silica sol were dissolved in 35000g pure water to obtain solution C. The aqueous solution of raw material A was added to the reactor, and the temperature of the reactor was maintained at 90°C. Under rapid stirring, the solution of raw material B was added to the reactor. After the precipitation impregnation was completed, aging was carried out, and then solution C was added. The frequency of the magnetic transmission of the supergravity machine is 30Hz, the temperature is 75℃, and the gravity acceleration is 38G. After supergravity pretreatment, the catalyst precursor is obtained, which is placed in an oven at 180℃ for 14 hours to obtain the catalyst precursor, and the catalyst powder is obtained after airflow classification. The formed strip catalyst is calcined at 550℃ for 10 hours to obtain the finished catalyst sample 5. The element ratio of sample 5 is shown in Table 1.
[0059] Oxidation test evaluation
[0060] The evaluation method is the same as that of Example 5, and the evaluation results are listed in Table 1.
[0061] Example 6
[0062] 70g of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O 24 ·4H20), 267g of iron nitrate (Fe(NO3)3·9H2O) were ultrasonically dissolved in 365g of pure water, and solution A was obtained after complete dissolution. 33.04g of CrO3 (chemical formula is CrO3), 124g of bismuth nitrate (chemical formula is Bi(NO3)3), and 60.1g of vanadium pentoxide (V2O5) were dissolved in 1500g of pure water to obtain solution B. Auxiliary agents 16.14g of cesium carbonate (chemical formula is Cs2CO3), 2.45g of magnesium nitrate (Mg(NO3)2), 4.82g of antimony trioxide, 30.5g of phosphoric acid, 9912g of 20% silica sol, and 16843.9g of 20% aluminum sol were used to obtain solution C. The aqueous solution of raw material A was added to the reactor, and the temperature of the reactor was maintained at 90°C. Under rapid stirring, the solution of raw material B was added to the reactor. After the precipitation impregnation is completed, aging is carried out, and then solution C is added. The frequency of the magnetic transmission of the supergravity machine is 37Hz, the gravity acceleration is 39G, and the temperature is 95℃. The catalyst precursor is obtained after supergravity pretreatment, and is placed in an oven at 170℃ for 16 hours to obtain the catalyst precursor. The catalyst powder is obtained after airflow classification. The catalyst precursor is crushed and sieved, and then calcined at 600℃ for 10 hours to obtain the finished catalyst sample 6. The element ratio of sample 6 is shown in Table 2.
[0063] Oxidation test evaluation
[0064] 25g of finished catalyst was loaded into a 50cm long reactor, where the reaction tube was a 25mm stainless steel reaction tube. The catalyst pretreatment process was as follows: firstly, air was introduced at a volume space velocity of 8000h -1 The temperature of the reaction tube was heated from room temperature to 250°C at a heating rate of 5°C / min and maintained for 120 min, then switched to nitrogen purge for 180 min at a purge volume space velocity of 1000 h -1 After the catalyst pretreatment is completed, methanol: oxygen: nitrogen: ammonia = 1:1.2:10:1.19 (molar ratio), volume space velocity 10000h -1 The amination reaction was carried out under the conditions of (standard state), temperature of 330°C and normal pressure. Reaction results: the initial methanol conversion rate was 98.7%, the hydrocyanic acid selectivity was 94.2%, and after 2000h of operation, the methanol conversion rate was 98.3%, and the hydrocyanic acid selectivity was 94%.
[0065] Example 7
[0066] 70g of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O 24 ·4H20), 0.99g chromium trioxide (CrO3) was ultrasonically dissolved in 365g pure water, and solution A was obtained after complete dissolution. 400.45g ferric nitrate (Fe(NO3)3·9H2O), 1.31g bismuth nitrate (chemical formula Bi(NO3)3), and 3g vanadium pentoxide (V2O5) were dissolved in 1000g pure water to obtain solution B. Auxiliary agents 2.7g cesium carbonate (Cs2CO3), 4956g 20% silica sol, 1684.4g 20% aluminum sol, 0.76g phosphoric acid, and 5.6g strontium nitrate (chemical formula Sr(NO3)2) were dissolved in 6000g pure water to obtain solution C. The aqueous solution of raw material A was added to the reactor, and the temperature of the reactor was maintained at 70°C. Under rapid stirring, the solution of raw material B was added to the reactor. After the precipitation impregnation is completed, aging is carried out, and then solution C is added. The frequency of the magnetic transmission of the supergravity machine is 36Hz, the temperature is 55℃, and the gravity acceleration is 13G. After supergravity pretreatment, the catalyst precursor is obtained, which is placed in an oven at 175℃ for 15 hours to obtain the catalyst precursor, and the catalyst powder is obtained after airflow classification. The catalyst precursor is crushed and sieved, and then calcined at 500℃ for 10 hours to obtain the finished catalyst sample 7. The element ratio of sample 7 is shown in Table 2.
[0067] Oxidation test evaluation
[0068] 25g of finished catalyst was loaded into a 50cm long reactor, where the reaction tube was a 25mm stainless steel reaction tube. The catalyst pretreatment process was as follows: firstly, air was introduced at a volume space velocity of 11000h -1 The temperature of the reaction tube was heated from room temperature to 250°C at a heating rate of 5°C / min and maintained for 120 min, then switched to nitrogen purge for 180 min at a purge volume space velocity of 1000 h -1 After the catalyst pretreatment is completed, propylene: ammonia: air = 1:1.1:12 (molar ratio), volume space velocity 1000h -1 The amination reaction was carried out under the conditions of (standard state), temperature of 400°C and normal pressure. Reaction results: the initial propylene conversion rate was 99.9%, the acrylonitrile selectivity was 90%, and after 2000h of operation, the propylene conversion rate was 99.6%, and the acrylonitrile selectivity was 89%.
[0069] Comparative Example 1
[0070] 70g of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O 24 ·4H20) was ultrasonically dissolved in 365g of pure water, and solution A was obtained after complete dissolution. 133.48g of iron nitrate (Fe(NO3)3·9H2O), 660.74g of CrO3 (chemical formula CrO3), 26.1g of bismuth nitrate (chemical formula Bi(NO3)3), and 540.84g of vanadium pentoxide (V2O5) were dissolved in 2600g of pure water to obtain solution B. 0.34g of potassium carbonate (K2CO3), 42.26g of nickel nitrate (chemical formula Ni(NO3)2), 4.41g of magnesium nitrate (Mg(NO3)2), 3.5g of strontium nitrate (Sr(NO3)2), and 59472g of 20% silica sol were dissolved in 50000g of pure water to obtain solution C. The aqueous solution of raw material A was added to the reactor, and the temperature of the reactor was maintained at 90°C. Under rapid stirring, the solution of raw material B was added to the reactor. After the coprecipitation, the aging process was performed for 8 hours, and the filter cake was filtered and washed to obtain the filter cake. The filter cake was dissolved in solution C, mixed evenly, placed in an oven at 90°C for 12 hours, and then heated to 180°C for 24 hours to obtain the catalyst precursor. The catalyst precursor was crushed and 2% sesbania powder and 0.6% graphite were added to extrude the strips to obtain a strip catalyst. The strip catalyst was calcined at 540°C for 10 hours to obtain a finished catalyst sample. The sample element ratio is shown in Table 2.
[0071] Oxidation test evaluation
[0072] The evaluation method is the same as that of Example 4, and the evaluation results are listed in Table 1.
[0073] Table 1 Evaluation results of catalysts in Examples and Comparative Examples
[0074]
[0075]
[0076] Table 2 Molar composition ratio of each element in the examples and comparative examples
[0077] Ratio of each element Example 1 <![CDATA[Mo 12 -R 150 Bi1V 240 That 0.2 K 0.5 P 18 And 8500 A 17623 ]]> Example 2 <![CDATA[Mo 12 Fe2Cr 250 Bi5V 120 Cs 0.2 K1P 25 If 5000 OH 10910 ]]> Example 3 <![CDATA[Mo 12 -R 280 Bi8V 250 Na3P 30 Ca1Sb3Si 8800 A 18915 ]]> Example 4 <![CDATA[Mo 12 Fe 10 Cr 200 Bi2V 180 K 0.15 You 6000 Ni7Sr 0.5 Mg 0.9 About 12913 ]]> Example 5 <![CDATA[Mo 12 Cr 80 Bi 0.1 V 240 Na 0.2 Cs 0.1 P5Sb2Sr 0.5 Yes 3000 About 6812 ]]> Example 6 <![CDATA[Mo 12 Fe 20 Cr 10 Would 9.5 In 20 Cs3P8Sb1Mg 0.5 Yes 1000 Al 2000 About 10348 ]]> Example 7 <![CDATA[Mo 12 Feb 30 Cr 0.3 Bi 0.1 V1Cs 0.5 Q 0.2 Sr 0.8 Si 500 Al 200 O 1386 ]]> Comparative Example 1 <![CDATA[Mo 12 Fe 10 Cr 200 Bi2V 180 K 0.15 You 6000 Ni7Sr 0.5 Mg 0.9 About 12913 ]]>
[0078] After 30 days of action of a flowing gas stream of 6% methanol and 8% ammonia, 8% oxygen and the remainder nitrogen at 300°C, no volatilization of bismuth or molybdenum from the catalyst of the present invention was detected.
Claims
1. A method for preparing an amination catalyst, characterized in that: The following steps are involved: a) adding a molybdenum source, a chromium source, a bismuth source, a vanadium source and an aqueous solution of an M source into a reaction kettle, and maintaining the temperature of the reaction kettle at 60° C. to 95° C.; b) adding the raw material solution to the reaction kettle under rapid stirring, controlling the pH value of the precipitation process to 1.0-3.0 with alkali or acid, and aging the precipitation for 2-12 hours after the precipitation is finished; c) mixing the catalyst solution evenly, adding the catalyst solution into a supergravity machine, performing supergravity pretreatment at a frequency of 10 Hz-35 Hz, a gravity acceleration range of 3-40 g, and a temperature of 50° C.-120° C. to obtain a catalyst precursor, and drying; d) calcining the catalyst powder at 400° C. to 600° C. for 10 to 20 hours to obtain a finished catalyst; M is one or more of Al, Na, K, Fe, P, B, Sb, Si, Ni, Pr, Mg, Cs, Nd, Ce, Ca, Ti, and Cu; Based on the molybdenum content of the molybdenum source being 12 parts by mole, the mole portion of chromium added to the chromium source is 0.3-300 parts by mole, The molar proportion of bismuth added to the bismuth source is 0.1-10 parts, The molar proportion of vanadium added to the vanadium source is 1-250 parts.
2. The preparation method according to claim 1, characterized in that: In step b), the pH value is controlled at 1 to 2.
8.
3. The preparation method according to claim 1, characterized in that: Based on the molybdenum content of the molybdenum source being 12 parts by mole, the mole portion of chromium added to the chromium source is 150-250 parts by mole.
4. The preparation method according to claim 1, characterized in that: The molar proportion of bismuth added to the bismuth source is 1-5 parts.
5. The preparation method according to claim 1, characterized in that: The molar proportion of vanadium added to the vanadium source is 120-240 parts.
6. The preparation method according to claim 1, characterized in that: The total added molar portion of the metal M in the M source is 0-9000 parts, wherein the added amount is not 0.
7. The preparation method according to claim 6, characterized in that: The total added molar portion of metal M in the M source is 5000-8600 parts.
8. The preparation method according to claim 1, characterized in that: The molybdenum source of the catalyst is selected from one or more of ammonium polymolybdate, molybdenum trioxide, molybdic acid and molybdenum disulfide.
9. The preparation method according to claim 8, characterized in that: The molybdenum source of the catalyst is selected from water-soluble molybdenum salt ammonium polymolybdate.
10. The preparation method according to claim 1, characterized in that: The chromium source of the catalyst is selected from one or more of chromium trioxide, dichromic acid, and chromium oxalate.
11. The preparation method according to claim 1, characterized in that: The vanadium source of the catalyst is selected from one or more of vanadium pentoxide, vanadium tetroxide, vanadium trioxide, ammonium metavanadate and sodium metavanadate.
12. The preparation method according to claim 11, characterized in that: The vanadium source of the catalyst is selected from vanadium pentoxide.
13. The preparation method according to claim 1, characterized in that: The bismuth source of the catalyst is selected from one or more of bismuth nitrate, bismuth carbonate or organic acid bismuth.
14. The preparation method according to claim 13, characterized in that: The bismuth source of the catalyst is bismuth nitrate.
15. The preparation method according to claim 1, characterized in that: In the step b), the stirring is performed rapidly, and the stirring speed is 50 r / min-1500 r / min.
16. The preparation method according to claim 15, characterized in that: In the step b), the stirring is performed rapidly, and the stirring speed is 200-800 r / min.
17. The preparation method according to claim 1, characterized in that: A magnetic actuator is provided in the ultra-gravity machine, the frequency of the magnetic actuator is 10Hz-35Hz, the gravity acceleration range is 3-40g, the temperature is 50℃-120℃, and the catalyst precursor is obtained after ultra-gravity pretreatment. The catalyst precursor is placed in an oven at 105℃-190℃ and dried for 10-28 hours to obtain the catalyst precursor, and the catalyst powder is obtained after airflow classification.
18. The preparation method according to claim 17, characterized in that: A packing layer is arranged inside the rotating device of the supergravity device.
19. The preparation method according to claim 1, characterized in that: In the step d), the calcination temperature is 400-550°C.
20. The preparation method according to claim 1, characterized in that: A reducing agent and an oxidizing agent are optionally added during calcination, wherein the reducing agent is selected from H2 and / or CO, and the oxidizing agent is selected from H2O and / or CO2.
21. The preparation method according to claim 1, characterized in that: During calcination, an inert agent is also added, and the inert agent is He, Ne, N2, Ar and / or Kr.
22. The preparation method according to claim 1, characterized in that: The gas volume compositions of reducing, oxidizing and inert agents are 0-50 vol.%, 0-50 vol.% and 99.99-0 vol.%, respectively.
23. The preparation method according to claim 1, characterized in that: The catalyst has 4-45m 2 / g specific surface area (BET).
24. The preparation method according to claim 23, characterized in that: The catalyst has 5-25m 2 / g specific surface area.
25. The preparation method according to claim 24, characterized in that: The catalyst has a 5.5-15m 2 / g specific surface area.
26. Use of the amination catalyst prepared by the preparation method according to any one of claims 1 to 25, which is used for the amination reaction of preparing nitriles from alcohols below C5, hydrocarbons below C5 or C7-C9 aromatic hydrocarbons.
Citation Information
Patent Citations
Ammonia oxidation catalyst, preparation method and application thereof
CN113893863A